2018
DOI: 10.1080/09593330.2018.1520307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the wetland environment on particulate matter and dry deposition

Abstract: In Beijing, particulate matter (PM) in the atmosphere, especially PM and PM, have attracted public attention because of its adverse effects. A series of studies have investigated the sources and spatial-temporal variation of PM. Wetland has been reported to own the capacity of resolving air problem. To examine the characteristics of the particulate matter in wetlands, the diurnal variation of PM and PM concentrations with respect to two heights (i.e. 1.5 and 10 m, respectively) and three meteorological factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…By contrast, in summer and autumn, the dry removal efficiencies of PM 10 and PM 2.5 during the night were significantly higher than those during the daytime; in addition, they were higher on the bare land and lower on the wetland. Although there was no significant difference between the dry removal efficiencies of PM 10 and PM 2.5 , on the whole, the dry removal efficiency of PM 10 was greater than that of PM 2.5 , which did conform with the results of Wu et al and Yang et al [60,61]. On the wetland, the dry removal efficiency of PM 10 followed the order of spring > winter > autumn > summer, similar to that of PM 2.5 , which was consistent with the results of Yang et al [61], whereas PM 10 and PM 2.5 dry removal efficiencies on the bare land ranked as autumn > summer > winter > spring.…”
Section: Removal Effectssupporting
confidence: 82%
See 4 more Smart Citations
“…By contrast, in summer and autumn, the dry removal efficiencies of PM 10 and PM 2.5 during the night were significantly higher than those during the daytime; in addition, they were higher on the bare land and lower on the wetland. Although there was no significant difference between the dry removal efficiencies of PM 10 and PM 2.5 , on the whole, the dry removal efficiency of PM 10 was greater than that of PM 2.5 , which did conform with the results of Wu et al and Yang et al [60,61]. On the wetland, the dry removal efficiency of PM 10 followed the order of spring > winter > autumn > summer, similar to that of PM 2.5 , which was consistent with the results of Yang et al [61], whereas PM 10 and PM 2.5 dry removal efficiencies on the bare land ranked as autumn > summer > winter > spring.…”
Section: Removal Effectssupporting
confidence: 82%
“…There was a negative relationship between the temperature and dry deposition of PM 10 and PM 2.5 : with the decrease of the temperature, the dry deposition increased, whereas the relative humidity had a positive effect on the dry deposition [23,45]. Inversely, Yang et al showed the influences of temperature and relative humidity on dry deposition were uncertain [61].…”
Section: Removal Effectsmentioning
confidence: 99%
See 3 more Smart Citations